Portfolio rebalancing and the dynamics between equity flow, exchange rates and equity returns - Chowdhury, Aysha Humayra (2018)
In this paper we use simple panel regression augmented by a VAR framework and impulse response function to test the presence of portfolio rebalancing between US and 7 developed countries. We find that overall portfolio rebalancing does hold, however some countries in the sample, specifically Australia and Canada display information asymmetry whereby US investors are less informed than local investors, and chase the returns in foreign markets during bullish times. We hypothesize that this phenomena and the increasing supply elasticity of the FOREX markets interfere with the explanatory power of equity flow over the portfolio rebalancing channel in the long term. We find that the portfolio rebalancing channel itself generates a fleeting exchange rate change, however the effect persists through two distinct channels of magnification, with the causality running from exchange rates to equity flow which further appreciates the USD. We hold that US faces a tradeoff between current account and capital account inflows. We also hold that equity flow can be an effective measure to assess foreign exchange intervention in the US only with currencies belonging to countries it has no information frictions with, and countries that have minimal intervention in their FOREX markets.